How Work From Home Boost Job Satisfaction on Women Workers? The Role of Work Life Balance as Mediating Variable - Fanelli, Finza; Erlin, Nia Ariyani (Pusat Studi Pembangunan dan Pemberdayaan, 2025)
The phenomenon of working women and working at home in Jakarta is Increasing. Previous study finds inconsistent the effects of work from home positively and negatively. This study investigates the effect of the work from home system on job satisfaction mediated by work life balance among female workers in Jakarta. This research using Social Exchange Theory (SET) as the grand theory. The study employs a quantitative approach with a causal research design involving 153 married female employees working remotely in Jakarta. Data were collected using google forms questionnaires and analyzed using SEM-PLS. The results reveal that work from home has a significant positive effect on job satisfaction and work life balance. Furthermore, work life balance significantly mediates the relationship between work from home and job satisfaction. These findings suggest that providing flexibility through work from home arrangements can enhance female employees’ work-life balance, leading to improved job satisfaction.